Social work administration and development - Bhattacharya, Sanjay (Jaipur Rawat Publications, 2006)
Social Work Administration and Development emphasizes upon the call for developing strategies and approaches to suit the new socio-economic reality by linking and integrating social skills with technical skills. It also covers the issues that are undertaken with regard to an individual, group and community in the process of organization and direction of a social institution. The increased participation of primary stakeholders can create confident communities, who are able to articulate their needs in a much better way and can contribute to the broader thinking and actions to develop support, monitor and evaluate interventions with government, civil societies and agencies. Discussing in details the key aspect of social welfare administration and developmental issues, the book attempts to create conceptual framework for the Indian realism. It is hoped that the reader will not only gain a perception of social welfare administration and development, but will also be able to approve and put into operation various practices in the organizations as well as institutional set-ups.
Keywords: Social development